2017
DOI: 10.1371/journal.pone.0178618
|View full text |Cite
|
Sign up to set email alerts
|

The role of reactive oxygen intermediates in the intracellular fate of Leptospira interrogans in the macrophages of different hosts

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
(70 reference statements)
3
10
2
Order By: Relevance
“…By opposition, in mice, leptospires do not trigger the recruitment of neutrophils in kidneys [25,15], although they recruit macrophages. Interestingly, a recent study showed that in murine macrophages, most of the killing of leptospires occurred through Reactive Oxygen Species (ROS), whereas L. interrogans barely stimulated ROS production in the THP-1 human macrophage cell line [26]. This is in line with a previous study from the same group showing cytosolic survival of leptospires in human macrophages, although murine macrophages would kill leptospires, present in vesicles [27].…”
Section: Complement/phagocytosis Escapesupporting
confidence: 84%
“…By opposition, in mice, leptospires do not trigger the recruitment of neutrophils in kidneys [25,15], although they recruit macrophages. Interestingly, a recent study showed that in murine macrophages, most of the killing of leptospires occurred through Reactive Oxygen Species (ROS), whereas L. interrogans barely stimulated ROS production in the THP-1 human macrophage cell line [26]. This is in line with a previous study from the same group showing cytosolic survival of leptospires in human macrophages, although murine macrophages would kill leptospires, present in vesicles [27].…”
Section: Complement/phagocytosis Escapesupporting
confidence: 84%
“… 15 , 50 Our recent study also confirmed that L. interrogans in macrophages could be killed by high level of reactive oxygen species. 51 Rodent animals, the most important host of L. interrogans , have a critical role in transmission of leptospirosis by persistent discharge of leptospires in urine to contaminate environment. 9 , 11 Therefore, we focused on the roles of protein denaturation and denatured protein elimination in survival of L. interrogans in murine macrophages after phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…The J774A.1 cell line was shown to produce NADPH oxidase and MPO during infections and on activation by drug treatment in vitro ( 55 , 65 ). Increased ROS levels significantly contributed to the antimicrobial activity and killing of intracellular pathogens by the J774A.1 macrophage cell line ( 54 ). Thus, MerA could be involved in the defense of S. aureus against ROS and HOCl also during macrophage infections.…”
Section: Discussionmentioning
confidence: 99%